Gender discourses and shifting subjectivities: examining women’s responses to intimate partner violence in Mombasa and Nairobi, Kenya - Isika, Victoria (2022)
Intimate partner violence (IPV) remains the most predominant form of violence experienced by women on a global scale. Nationally representative statistics reveal telling rates in Kenya, but relatively little empirical attention has been devoted to exploring the phenomenon qualitatively in this context. This thesis narrows this gap in the academic literature by investigating the experiences of IPV among 28 women from Mombasa and Nairobi, with particular focus on their responses and coping mechanisms within marital or cohabiting relationships. It applies primarily post-structural feminist insights on discourses and subjectivities to investigate how women’s responses to IPV conformed to, or deviated from, dominant representations of femininity in Kenya. Post-structural feminism has been minimally employed to frame our understanding of the experiences of IPV among women in sub-Saharan Africa. Therefore, the integration of these conceptual elements into the study addresses the limited theoretical application with special focus on Kenya. In addition, insights from Black and African feminism are incorporated to evaluate critically how gender is interlinked with other axes of disadvantage to inform women’s behaviours in an atmosphere of IPV. The thematic and discourse analytical approaches found diverse and contradictory feminine portrayals, most of which stood in contrast with mainstream representations of African women as being demure, accepting and quiescent recipients of male abuse and mistreatment. Therefore, this thesis highlights Kenyan women’s efforts in mitigating the effects of IPV by exploring how their resourcefulness was concealed behind docile and deferential behaviour. In addition to investigating these strategically passive femininities, this study also draws attention to women’s overt subversion of the traditional gender script that was evident in their unruly, outspoken, defiant and aggressive conduct in conjugal settings. Throughout these revealing narratives of unorthodox behaviour, the thesis attempts to identify Kenyan women’s subtle and explicit processes of revising oppressive regimes that have historically validated their subsidiary position to men in domestic and intimate environments. Ultimately, the research offers insights into understanding women’s subjectivities as being protean in the unpredictable IPV milieu. This understanding is instrumental in informing policy and programmes to prevent IPV in Kenya and the rest of sub-Saharan Africa.